2014
DOI: 10.1128/mbio.01001-13
|View full text |Cite
|
Sign up to set email alerts
|

The SMC Complex MukBEF Recruits Topoisomerase IV to the Origin of Replication Region in Live Escherichia coli

Abstract: The Escherichia coli structural maintenance of chromosome (SMC) complex, MukBEF, and topoisomerase IV (TopoIV) interact in vitro through a direct contact between the MukB dimerization hinge and the C-terminal domain of ParC, the catalytic subunit of TopoIV. The interaction stimulates catalysis by TopoIV in vitro. Using live-cell quantitative imaging, we show that MukBEF directs TopoIV to ori, with fluorescent fusions of ParC and ParE both forming cellular foci that colocalize with those formed by MukBEF throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 44 publications
10
92
0
Order By: Relevance
“…Colocalization of sister loci behind the fork is usually thought to involve “precatenanes”, topological intertwining between sisters that would be driven by alleviation of the replication “swivel problem” [3437]. Catenated sisters have been observed directly on small plasmids and linking of sisters by precatenanes has been inferred for the main chromosome from the fact that absence of TopoIV results in aberrant segregation and delayed locus splitting [27,35,38].…”
Section: The Nucleoidmentioning
confidence: 99%
“…Colocalization of sister loci behind the fork is usually thought to involve “precatenanes”, topological intertwining between sisters that would be driven by alleviation of the replication “swivel problem” [3437]. Catenated sisters have been observed directly on small plasmids and linking of sisters by precatenanes has been inferred for the main chromosome from the fact that absence of TopoIV results in aberrant segregation and delayed locus splitting [27,35,38].…”
Section: The Nucleoidmentioning
confidence: 99%
“…Additionally, a major challenge is to determine whether MukBEF promotes chromosome segregation indirectly by condensing DNA, which may make other mechanisms of segregation operate more efficiently, or whether the MukBEF complex plays a more active role in directly partitioning sister chromosomes. Recent studies have demonstrated that MukBEF directly stimulates Topo IV, implying that MukBEF contributes to the disentangling of sister chromosomes (Hayama & Marians 2010, Li et al 2010, Nicolas et al 2014). …”
Section: Bacterial Chromosome Segregationmentioning
confidence: 99%
“…A weak interaction between MukB and ParC was recently discovered using co-immunoprecipitation [Hayama and Marians, 2010; Li et al, 2010b]. This interaction is sufficiently selective to discriminate between topo IV and DNA gyrase [Vos et al, 2013] and sufficiently strong to recruit a subset of topo IVs to the quarter positions inside the cell [Nicolas et al, 2014]. Mutations that disrupt MukB-ParC interface adversely affect such localization and E. coli viability [Hayama and Marians, 2010; Li et al, 2010b].…”
Section: Beyond Scaffold: Recruit and Be Recruitedmentioning
confidence: 99%